Potensi Perkembangan Halal Food di Denpasar Bali - Rifky Setiawan; Muhammad Mirza Pahlevi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2023)
This study provides a clear description of the word halal and some activities related to Halal Tourism. Halal tourism which is a sub-category of tourism aimed at Muslim families who adhere to Islamic rules. In addition, it is expected to know that halal tourism is very good for supporting and creating jobs and foreign exchange which is quite high, moreover it is developed with an environmentally friendly sustainable concept. And from this research it can be concluded how big the potential for developing halal food is in Denpasar, Bali.